Single molybdenum atom anchored on 2D Ti2NO2 MXene as a promising electrocatalyst for N2 fixation - Cheng, Yuwen; Dai, Jianhong; Song, Yan; Zhang, Yumin (Nanoscale, 2019)
The electrocatalytic synthesis of ammonia (NH3) at ambient temperature is an attractive and challenging subject in the chemical industry. The synthesis of NH3 under ambient conditions requires efficient and stable electrocatalysts with ultralow overpotential to ensure low energy consumption and high NH3 yield. Herein, electrocatalysts consisting of a single transition metal (TM) atom (TM = Mo, Mn, Fe, Co, Ni, or Cu) anchored on 2D M2NO2 MXene (M = Ti, V, and Cr), designated as TM/M2NO2, are designed for N2 reduction reaction (NRR) by density functional theory calculations. The results show that the bonding strength between Mo and Ti2NO2 is strong. The overpotential (ηNRR) of Mo/Ti2NO2 surface-catalyzed NRR is estimated to be as low as 0.16 V via an enzymatic mechanism, which is lower than those reported to date. For Mo/V2NO2 and Mo/Cr2NO2 catalysts, the NRR occurs through the consecutive mechanism and enzymatic mechanism, with corresponding ηNRR values of 0.38 V and 0.22 V, respectively. In addition, the reaction Gibbs free energy of NH3 desorption from the Mo/Ti2NO2 surface is only 0.12 eV. Electronic structure analysis indicates that Mo/Ti2NO2 shows metallic characteristics, which ensures the efficient transfer of electrons between Mo and Ti2NO2. Ab initio molecular dynamics simulations indicate that the Mo atom can be stably immobilized on the Ti2NO2 substrate to prevent its aggregation into Mo clusters. Further analysis illustrates that hydrogen adsorption is not favored on the Mo/Ti2NO2 surface. Mixing the N2 source with extra gases, such as NO2, NO, SO2, SO, and O2, should be avoided for NRR on Mo/Ti2NO2 surface. These predictions offer a new opportunity for the electrocatalytic synthesis of NH3 by N2 reduction in the future.